2020
DOI: 10.15414/jmbfs.2020.9.4.844-847
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria May Deteriorate Progressive Motility of Bovine Spermatozoa and Biochemical Parameters of Seminal Plasma

Abstract: Bacterial contamination of ejaculates has captured the interest of the wide andrological community. Interactions between spermatozoa and bacteria are partially known. The aim of our study was to evaluate qualitative bacterial composition of fresh bovine semen and to reveal associations amongst the quantity of bacteria (Colony Forming Unit – CFU/mL) present in bovine ejaculates with progressive motility of spermatozoa and biochemical parameters of seminal plasma. Fresh semen (n=20) was collected from Holstein-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…This study was built on the premises of our previous studies which reported that Staphylococcus species are highly represented in bovine semen with a decline in spermatozoa quality [ 1 , 2 , 11 ]. Semen samples were processed using the Percoll ® Plus density gradient medium and separated sperm pellets were individually contaminated by the Staphylococcus species in the presence of DPBS with MgCl 2 and CaCl 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was built on the premises of our previous studies which reported that Staphylococcus species are highly represented in bovine semen with a decline in spermatozoa quality [ 1 , 2 , 11 ]. Semen samples were processed using the Percoll ® Plus density gradient medium and separated sperm pellets were individually contaminated by the Staphylococcus species in the presence of DPBS with MgCl 2 and CaCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [ 11 ] found out correlations between the presence of bacteria in bovine ejaculates and biochemical composition of seminal plasma. Especially, Mg seminal concentration acted as a critical parameter in terms of the bacterial presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the bovine urogenital microbiome is has not been fully described or understood, especially in the case of males [ 25 ]. A previous study on the identification of bacterial presence in the semen of Holstein Friesian bulls used blood agars, Gassner agars and Tryptic soy agars, identifying the following bacteria: Bacillus cereus, Staphylococcus cohnii, Staphylococcus klosii, Micrococcus luteus, Bacillus licheniformis, Staphylococcus xylosus, Staphylococcus aureus, Staphylococcus warneri, Staphylococcus lentus, Staphylococcus epidermidis, Bacillus mycoides and Staphylococcus haemolyticus [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a minimum of 60–70% motility is required as optimal for boar or bovine spermatozoa to further processing [ 40 , 41 ]. However, analysis of ram semen samples in our study showed that the sperm viability of some samples was poor, even if their motility was relatively high (over 70%, data not shown).…”
Section: Discussionmentioning
confidence: 99%